PEMBELAJARAN BAHASA PADA ANAK USIA DINI MELALUI CERITA BERGAMBAR - Much Deiniatur (Jurusan PGMI FTIK IAIN Metro Lampung, 2017)
Language Skill consists of four components of speaking, writing, listening and reading. The most important thing for children is speaking, because it provides enormous benefits, one of which so that children can interact with peers and others around them and add new knowledge. Storytelling is a popular communication medium for children, training their ability to focus attention for some time on certain objects. Children are able to express themselves through a process that makes them happy and fosters a sense of satisfaction that makes them more confident. Tale or story telling is something human, that is, fairy tale or story using eye, hearing, motion, and touching heart. The benefits of storytelling activities are: 1.) Storytelling can develop children's imagination, 2.) Increasing experience, 3.) Train concentration power, 4.) Increasing the vocabulary, 5.) Creating a familiar atmosphere, 6.) comprehending, 7.) Developing social feelings, 8.) Developing children's emotions, 9.) Practicing listening, 10.) Knowing positive and negative values. 11.) Adding knowledge Keywords: language, early childhood, story, picture